FTIR nanobiosensors for Escherichia coli detection - Mura, Stefania; Greppi, Gianfranco; Marongiu, Maria Laura; Roggero, Pier Paolo; Ravindranath, Sandeep P.; Mauer, Lisa J.; Schibeci, Nicoletta; Perria, Francesco; Piccinini, Massimo; Innocenzi, Plinio; Irudayaraj, Joseph (Beilstein Journal of Nanotechnology, 2012)
Infections due to enterohaemorrhagic E. coli (Escherichia coli) have a low incidence but can have severe and sometimes fatal health consequences, and thus represent some of the most serious diseases due to the contamination of water and food. New, fast and simple devices that monitor these pathogens are necessary to improve the safety of our food supply chain. In this work we report on mesoporous titania thin-film substrates as sensors to detect E. coli O157:H7. Titania films treated with APTES ((3-aminopropyl)triethoxysilane) and GA (glutaraldehyde) were functionalized with specific antibodies and the absorption properties monitored. The film-based biosensors showed a detection limit for E. coli of 1 × 102 CFU/mL, constituting a simple and selective method for the effective screening of water samples.
Keywords: biosensors; E. coli; FTIR spectroscopy; foodborne pathogens; nanomaterials